2011
DOI: 10.1111/j.1463-6409.2011.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative inventory of Bolivia’s lowland anurans reveals hidden diversity

Abstract: Pfenninger, M. (2011). Integrative inventory of Bolivia's lowland anurans reveals hidden diversity. -Zoologica Scripta, 40, 567-583. We conducted an integrative species inventory and re-evaluated the taxonomic status of anuran populations from lowland Bolivia that we putatively ordered to 59 a priori species. The analyses of own and published data of mtDNA (16S), bioacoustics, and adult and tadpole morphology, however, revealed a total number of 69 divergent lineages. With the data at hand, the taxonomic assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 97 publications
7
114
0
4
Order By: Relevance
“…This placement agrees with the results of Fouquet et al (2013), although those authors indicated that adequate sampling within Leptodactylus, Adenomera, and Hydrolaetare was needed to test the monophyly of these genera. Our results also agree with Jansen et al (2011), although only if their neighbor-joining tree is re-rooted on any leiuperid instead of within Leptodactylus. The close relationship between Hydrolaetare and Leptodactylus is not unexpected.…”
Section: Overview and Outgroup Relationshipssupporting
confidence: 86%
“…This placement agrees with the results of Fouquet et al (2013), although those authors indicated that adequate sampling within Leptodactylus, Adenomera, and Hydrolaetare was needed to test the monophyly of these genera. Our results also agree with Jansen et al (2011), although only if their neighbor-joining tree is re-rooted on any leiuperid instead of within Leptodactylus. The close relationship between Hydrolaetare and Leptodactylus is not unexpected.…”
Section: Overview and Outgroup Relationshipssupporting
confidence: 86%
“…When advertisement calls are described for species that have already been named, it is recommendable to obtain recordings from their type locality (as well as obtaining topotypic voucher specimens), as this increases the chances of actually describing the call of a particular nominal species. However, in the latter case, careful morphological comparisions of newly collected call vouchers and original type specimens is warranted, as (cryptic) diversity at a single locality can be unexpectably high, particularly in the tropics (e.g., Jansen et al 2011;Gehara et al 2014;Fouquet et al 2016).…”
Section: Voucher Specimens and Photosmentioning
confidence: 99%
“…At the level of species, a similar revolution is taking place with the incorporation and popularization of molecular data as a crucial component of integrative taxonomy (Dayrat 2005;Padial et al 2010). This led to an enormous acceleration in the rate of species discovery in numerous groups of organisms (e.g., Bickford et al 2007;Pfenninger & Schwenk 2007;Fontaneto et al 2008;Fonseca et al 2010;Poulin 2011;Stuart et al 2006;Oliver et al 2009;Vieites et al, 2009;Jansen et al 2011;Funk et al 2012). Estimates usually agree that only a fraction of Earth's species diversity has so far been inventoried and taxonomically described, with a possible 86% of existing species on Earth and 91% of species in the oceans still awaiting description (Mora et al 2011).…”
Section: Introductionmentioning
confidence: 99%